The role of the pharmacist in a multidisciplinary oncology team: integrative review (Research, Society and Development, 2022)
The pharmaceutical performance in oncology has been debated over the years, seeking to enhance the contributions of this professional to the multidisciplinary team and to the patient. This work aimed to study the professional perceptions of a pharmaceutical professional working in a hospital oncology area. The methodology used is a structured interview carried out remotely, containing open questions that leave the interviewee free to answer openly about their performance. In relation to the results obtained, it is noteworthy that all questions were answered and indicate, in general, that the professional's performance follows a context that demands knowledge, technical and emotional preparation, in addition to a humanized performance. It is concluded that the pharmacist in the oncology area contributes significantly to obtaining a more favorable scenario for the improvement of the patient. Its performance ranges from the preparation of medicines to direct contact with patients to clarify doubts and reassure about the drugs that are being used.